2006
DOI: 10.1007/s11596-006-0519-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of subcutaneous administration of gonadotropin-releasing hormone agonist on idiopathic central precocious puberty

Abstract: In order to assess the feasibility of subcutaneous administration of Triptorelin with 6-week intervals for the suppression of pituitary-gonadal axis and changes of clinical signs in girls with idiopathic central precocious puberty (ICPP), 46 girls with ICPP were treated with GnRHa. Triptorelin (Decapeptyl, 3.75 mg) was administered subcutaneously (SC) at 6-weeks intervals or intramuscularly (IM) at 4-weeks intervals randomly for more than 12 months consecutively. During GnRHa therapy, clinical parameters and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…32 Furthermore, a study comparing the same formulation of triptorelin delivered via SC versus IM found that SC was equally effective as a mode of administration as IM, with a favorable safety profile. 33 There were several limitations to this study. Healthy subjects were enrolled and T suppression may be more difficult than in PCa patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…32 Furthermore, a study comparing the same formulation of triptorelin delivered via SC versus IM found that SC was equally effective as a mode of administration as IM, with a favorable safety profile. 33 There were several limitations to this study. Healthy subjects were enrolled and T suppression may be more difficult than in PCa patients.…”
Section: Discussionmentioning
confidence: 94%
“…32 Furthermore, a study comparing the same formulation of triptorelin delivered via SC versus IM found that SC was equally effective as a mode of administration as IM, with a favorable safety profile. 33…”
Section: Discussionmentioning
confidence: 99%
“…In the literature the incidence of bleeding at the beginning of treatment with GnRHa for ICPP varies from 0 to 60% depending on the number and age of the children enrolled and on the method of treatment administration [2,4,12,13,14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…In the study by Liang et al [17], 46 girls were recruited and treated with subcutaneous or intramuscular triptorelin; 2 of 46 (4%) suffered from one episode of mild endometrial bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Un ensayo clínico 43 encontró que la vía de administración de la triptorelina de depósito (subcutánea versus intramuscular) no parece modificar su efectividad en cuanto a los desenlaces clínicos, pero no existen datos de la talla adulta. (Nivel de evidencia: 1− SIGN.)…”
Section: Dosisunclassified